Current landscape of cancer genomics research in sub-Saharan Africa – a review of literature - Amaeshi, Lemchukwu C.; Okunade, Kehinde S.; Anorlu, Rose I. (Frontiers in Oncology, 2025)
Cancer poses a significant public health challenge in sub-Saharan Africa, a region that has traditionally struggled with infectious diseases. Although communicable diseases remain the leading cause of mortality in sub-Saharan Africa (SSA), there has been a rise in the morbidity and mortality rates associated with non-communicable diseases (NCDs), in recent years. As of 2019, NCDs accounted for 37% of deaths, representing an increase from the 24% recorded in 2000. Cancer is fundamentally a genetic disorder, and genomic research has provided a deeper understanding of its biology leading to identification of biomarkers for early cancer detection and advancement in precision oncology. However, despite Africa’s rich genomic diversity and significant cancer burden, the continent remains underrepresented in global genomic research. This underrepresentation is mainly due to challenges such as insufficient funding, inadequate infrastructure, and a limited pool of trained professionals. However, despite these obstacles, initiatives like the H3Africa Consortium, African BioGenome Project, and Prostate Cancer Transatlantic Consortium (CaPTC), amongst others, have made significant strides in funding and developing local capacity and infrastructure for genomic research. In this review, we discuss the unique genomic characteristics of common cancers in Africa, highlight challenges faced in the implementation of genomic research, and explore potential solutions and current initiatives instituted to foster genomic research in the region.